Phosphorus recovery through adsorption by layered double hydroxide nano-composites and transfer into a struvite-like fertilizer. (15th November 2018) - Yan, Hanlu; Chen, Qiuwen; Liu, Jinhua; Feng, Yong; Shih, Kaimin
Abstract: Phosphorus (P) recovery from waste streams is attracting more attention due to the twin problems of aquatic eutrophication and global phosphorus scarcity. Layered double hydroxide mineral materials are promising phosphate adsorbents due to their excellent anion-exchange abilities and large surface area. In this study, the adsorption isotherms estimated the saturation capacity of calcined layered double hydroxide (LDH) nano-composites for phosphate as 100.7 mg-P/g-adsorbent. Ion exchange is proposed as the major mechanism in the sorption process. The commonly utilized desorption method via sodium hydroxide was found to cause recrystallization of LDH particles in increased crystal size based on the dissolution-reprecipitation (D-R) mechanism. Ammonia solution was used to desorb P from LDH adsorbent. However, struvite crystallization occurred during the desorption process because struvite has a higher precipitation tendency than LDH with sufficient NH4 + ions. The comparison of P leaching behavior among P-adsorbed LDH, ammonia-treated LDH, and pure struvite samples demonstrates that ammonia desorption probably weakened the interaction between phosphate species and LDH cationic layers, thus enhancing the bioavailability of P in LDH adsorbents. The ammonia-treated LDH has a high potential to serve like struvite as a P slow-releasing fertilizer. Graphical abstract: Image 1 Highlights: Calcined Mg-Al LDH nano-composites showed high saturation capacity for P sorption. Desorption by NaOH caused recrystallization of LDH in increased crystal size. Struvite crystallization occurred during the desorption of LDH by ammonia. P distribution in related phases of ammonia treatment was quantitatively analyzed. Ammonia treated LDH products showed P slow-releasing property like struvite.